1992
DOI: 10.1128/aac.36.9.1810
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of human pharmacokinetics of panipenem-betamipron, a new carbapenem, from animal data

Abstract: The pharmacokinetic behavior of panipenem (PAPM)-betamipron (BP), a new carbapenem, in humans was successfully predicted from data collected from six animal species. PAPM and BP were biphasically eliminated from plasma after intravenous (i.v.) administration of PAPM-BP to mice, guinea pigs, rats, rabbits, monkeys, and dogs. Elimination rates of PAPM and BP were correlated with animal size: the larger the animal was, the slower the elimination was. As for PAPM and BP, log-log plots of total plasma clearance (CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…3 and Table 2, respectively) were similar to those reported in previous studies. 3,13 These results suggest that the clinical monitoring of carbapenem levels is possible with our HPLC method.…”
Section: Discussionmentioning
confidence: 88%
“…3 and Table 2, respectively) were similar to those reported in previous studies. 3,13 These results suggest that the clinical monitoring of carbapenem levels is possible with our HPLC method.…”
Section: Discussionmentioning
confidence: 88%
“…The steady-state distribution volume of panipenem in a human of mass 60 kg was calculated using the equation given above as V SS,hum = 12.1 (5.9 -25.1) L. The V SS for humans that was obtained earlier [62] from pharmacokinetic data was 11.1 L, which indicated that the accuracy of the extrapolation was fully satisfactory. The parameters of interspecies distribution volume functions were determined for many drugs using Eq.…”
Section: Interspecies Functions For Drug Distribution Volumesmentioning
confidence: 99%
“…For example, consider the interspecies function for the steady-state distribution volume of the antibiotic panipenem, which we constructed previously [62]. The drug pharmacokinetic parameters for six animal species were calculated from (2 ).…”
Section: Interspecies Functions For Drug Distribution Volumesmentioning
confidence: 99%
“…mice, rats, rabbits and dogs, to investigate interspecies correlation and to predict human pharmacokinetics of the drug. Several reports concerned with animal scale-up of pharmacokinetic parameters of panipenem-betamipron [14], DA-1131, a new carbapenem [15], SJ-8029, a new anticancer agent [16], lamifiban, a new platelet aggregation inhibitor [17] and amphotericin B [18] by allometric scaling have been published. The purpose of this paper is to report the pharmacokinetics of oltipraz after intravenous and/or oral administration with various doses to mice, rats, rabbits and dogs, and to investigate the interspecies relationship of pharmacokinetic parameters of oltipraz, such as the time-averaged total body clearance (Cl) Â maximum life-span potential (MLP), Cl, and apparent volume of distribution at steady state (V ss ), and to predict the pharmacokinetics of the drug in humans from the four animal data.…”
Section: Introductionmentioning
confidence: 99%